BUDAYA ORGANISASI, PERILAKU DISFUNGSIONAL DAN KINERJA PADA TAHAP PERENCANAAN ANGGARAN - S. Hikmah Jamil (BAJ: Behavioral Accounting Journal, 2019)
This research aimed to explained the effect of dysfungtional behavior as mediator variabel that correlated organizational behavior and public servant performance. This research use explanatory research, objected to local government of Sumenep, Indonesia. This research use a quantitative approach, with data collection techniques using questionnaires. The population in this study were all structural officials who worked in the official offices in Sumenep Regency which consisted of 16 official offices. From 317 questionnaires distributed to respondents, only 162 questionnaires can be processed and become research samples. Data were analyzed using Partial Least Square (PLS). The result showed no effect of participation budgeting on the performance of the apparatus either directly or through the dysfungtional behavior as a moderating variable. While the organizational culture give effect to the performance of the apparatus and dysfungtional behavior directly. This research found that dysfungtional behavior has not been able to moderate the relation of budgeting participation and oganizational culture on the performance of local apparatus. Organizational culture can effect the performance of the officers and officials dysfungtional behavior. Organizational culture give more effect to the participation of budgeting on the performance of local apparatus.